Omicron N501Y mutation among SARS-CoV-2 lineages: Insilico analysis of potent binding to tyrosine kinase and hypothetical repurposed medicine. Issue 45 (January 2022) - Kazybay, Bexultan; Ahmad, Ashfaq; Mu, Chenglin; Mengdesh, Diana; Xie, Yingqiu
Abstract: Variants of SARS-CoV-2 lineages including the most recently circulated Omicron, and previous pandemic B.1.351, B.1.1.7, which have been public concerns, contain a N501Y mutation located in the spike receptor binding domain. However, the potential interactions with host cells linking N501Y mutation to pathogenic relevance remain elusive. Recently, we and others report that kinases such as PI3K/AKT signaling are essential in SARS-CoV-2 entry. Here we analyzed the predicted potential kinases interacting with the mutation. Bioinformatics tools including structure-prediction based molecular docking analysis were applied. We found kinases such as EGFR might potentially act as new factors involving the N501Y mutation binding through possible phosphorylation at Y501 and enhanced affinity in certain variants. To our surprise, the Omicron receptor binding domain harboring N501Y mutation did not enhance binding to EGFR which might be due to the mutations of charged polar to uncharged polar side chains located on the interaction interfaces. Similarly, potent gains of phosphorylation in B.1.351 and B.1.1.7 by mutations were predicted and interaction networks were analyzed with enrichment of pathways. Given kinases might be elevated in cancer patients, the N501Y mutation containing lineages may be possibly much more infectious and additional care for cancer management might be taken into consideration by precision prevention, therapy or recovery.